2022
DOI: 10.3389/fnins.2022.838055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 3-Week Heartbeat Perception Training on Interoceptive Abilities

Abstract: Recent studies showed promising short-term effects of heartbeat perception training on interoceptive abilities. Research on the effects of heartbeat perception training on interoceptive abilities over time is sparse. Therefore, the aim of this study was to examine the short-term effects and the effects of a 3-week heartbeat perception training over time on interoceptive abilities, namely, cardiac interoceptive accuracy (IAc) and interoceptive sensibility (IS). A total of 40 healthy participants were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 92 publications
4
6
2
Order By: Relevance
“…These changes were also unrelated to interindividual differences in IAcc: the IAcc increase was not associated with baseline levels of IAcc (Supplementary Material S4). This reduction, is, however, in line with previous studies observing a reduction in IAcc with time, unless manipulations to increase the internal focus of attention (e.g., providing feedback about the performance) are carried out (Quadt et al, 2021;Schillings et al, 2022). Importantly, our findings concord with recent reports on the effects of taVNS on IAcc.…”
Section: Mediation Analysissupporting
confidence: 93%
“…These changes were also unrelated to interindividual differences in IAcc: the IAcc increase was not associated with baseline levels of IAcc (Supplementary Material S4). This reduction, is, however, in line with previous studies observing a reduction in IAcc with time, unless manipulations to increase the internal focus of attention (e.g., providing feedback about the performance) are carried out (Quadt et al, 2021;Schillings et al, 2022). Importantly, our findings concord with recent reports on the effects of taVNS on IAcc.…”
Section: Mediation Analysissupporting
confidence: 93%
“…In contrast with previous studies (Meyerholz et al, 2019;Schillings et al, 2022) The observed superiority of naturalistic haptic vs. visual feedback can also be explained within the context of the concept and theory of predictive coding (Apps & Tsakiris, 2014;Owens et al, 2018).…”
Section: Implications For Sensory Researchcontrasting
confidence: 85%
“…Using this procedure, they showed improved heartbeat perception, but moreover, their findings indicated a link between lower cardioceptive accuracy and greater symptom severity in sufferers of these disorders. Several studies have since employed similar cardiac biofeedback methods based on visual feedback by way of a symbolic representation of a heart, such as Meyerholz et al (2019), Schillings et al (2022) showing increased cardioceptive awareness following the training (Meyerholz et al, 2019; Schillings et al, 2022). Besides improving interoception, cardioceptive training has been shown to decrease anxiety in autistic adults (Quadt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies showed that interoceptive abilities are associated with emotional abilities (e.g., 22,23) and that they are impaired in diverse mental disorders such as anorexia nervosa (e.g., 24), depression (e.g., 25), or schizophrenia (26). An increasing body of research indicates that interoceptive abilities can be trained, for example, via mindfulness-based interventions (e.g., 27,28), bodyfocused training such as power posing (29), or heartbeat perception training (30,31). So far, online interventions to improve interoceptive abilities are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…An ongoing study (32) investigates the effects of a guided online mindfulness-based intervention on stress, interoceptive abilities and further health-related parameters. Integrating such trainings into everyday life might be a promising approach (31).…”
Section: Introductionmentioning
confidence: 99%